In vitro growth of Cattleya guttata and Epidendrum schomburgkii with acid silicate - Mantovani, C. [UNESP]; Galdiano, R. F. [UNESP]; Delgado, J. M. [UNESP]; Prado, R. M. [UNESP]; Pivetta, K. F.L. [UNESP] (International Society for Horticultural Science (ISHS), 2018)
The choice of suitable source and concentration of silicon added to culture medium may benefit orchid seedling production. Therefore, this work aimed to evaluate growth of Cattleya guttata and Epidendrum schomburgkii seedlings grown in vitro under acid silicate concentrations. This silicon source contains 14.04 g L-1 of silicon as sodium silicate, hydrochloridric acid 10%, water pH=11 and polyethylenoglycol 400. Protocorms 90-day-old grown on Murashige and Skoog medium were transferred onto MS medium containing the acid silicate in seven different concentrations (treatments) of 0, 1, 2, 4, 6, 8 and 10 mL L-1; and four replicates in a completely randomized experimental design. The seedlings were transferred to 280-mL flasks with 40 mL of the nutrient media and incubated under controlled conditions of temperature (24-27°C) and illumination (25 μmol m-2 s-1 with photoperiod of 14 h light). After 90 days of in vitro growth (180 days after sowing), leaf number, root number, root length, shoot height, leaf area and total dry matter mass were evaluated. Data were submitted to analysis of variance (ANOVA) and the means compared by the Tukey’s test at 5% of probability using the Agroestat statistical program. The concentration of 10 mL L-1 of the acid silicate is recommended as an additive in the culture medium for Cattleya guttata and Epidendrum schomburgkii, as it improved all the growth parameters evaluated.
Keywords: Floriculture; Micropropagation; Orchid; Seedling production; Silicon